Pengaruh Doping Strontium pada Lapisan Tipis BaZr0.20 Ti0.80O3: D. F. Saputri, S. Hadiati, A. H. Ramelan, Y. Iriani, V. Inda Variani - D. F. Saputri, D. F. Saputri; S. Hadiati, S. Hadiati; A. H. Ramelan, A. H. Ramelan; Y. Iriani, Y. Iriani; V. Inda Variani, V. Inda Variani (Jurnal Fisika dan Aplikasinya, 2025)
A thin layer of Barium Zirconium Titanate (BaZr0.20 Ti0.80O3) doped strontium (Sr) 1% and 3% have been successfully grown on a substrate Pt/Si. A thin layer deposited using Chemical Solution Deposition (CSD) were prepared by spin coater with a rotational speed of 4000 rpm and a annealing temperature of 8000 C. The XRD characterization results indicate peaks belonging BZT and a shift in the peak after doped Sr. Refinement by the Rietveld analysis using GSAS program shows that Sr atoms were incorporated in BZT and the results of the analysis showed the lattice parameter increase with increasing Sr. The results indicate SEM characterization of thin film surface BSZT has been deposited on the substrate Pt/Si and as the Sr concentration increases, the grain size decreases.